Optimized Extraction of cAMP From Jujube by Ultra-High Pressure Technology and the Anti-allergic Effect for Peanut Allergy Mouse - Sang, Chaowei; Bai, Qiao; Feng, Xiaoping; Wu, Chunyu; Liu, Ye; Gao, Zhenpeng; Long, Fangyu (Frontiers in Nutrition, 2022)
Jujube contains abundant cyclic adenosine monophosphate (cAMP). In contrast, the extraction technology of cAMP from jujube is still to be explored. In this study, the ultra-high pressure extraction (UHPE) conditions for obtaining the maximum cAMP yield from jujube were optimized. Orthogonal array design (OAD) was applied to evaluate the effects of three variables (pressure, pressure-holding time and liquid to solid ratio) by UHPE on cAMP yield. The results showed that the optimal cAMP yield (1223.2 μg/g) was derived at 300 MPa, 20 min duration and a liquid to solid ratio of 2.5 mL/g. In addition, as an important functional ingredient in jujube, cAMP has potential anti-allergic effect. To develop the functional characteristics of jujube, the effect of cAMP was characterized in vivo with a Balb/c mouse model of peanut allergy, which was established by subcutaneous injection of crude peanut protein extract (PN). The results showed treatment with cAMP in PN-sensitized mice suppressed the lesions in jejunal tissues and allergic symptoms, and restored spleen index. Meanwhile, cAMP reduced serum levels of specific immunoglobulin E (IgE), histamine as well as interleukin-4 (IL-4) and stimulated the secretion of tumor necrosis factor-α (TNF-α), whereas the serum levels of interleukin-10 (IL-10) were not affected. Our results suggested that cAMP has an anti-allergic effect in PN-sensitized mice.